Whole-genome analysis of the recombination and evolution of newly identified NADC30-like porcine reproductive and respiratory syndrome virus strains circulated in Gansu province of China in 2023 - Jiao, Shoude; Zhang, Jing; Wang, Jian; Ma, Xueqing; Li, Guoxiu; Li, Jiaoyang; Cui, Zhanding; Li, Dong; Li, Pinghua; Zeng, Qiaoying; Liu, Zaixin; Lu, Zengjun; et al. (Frontiers in Veterinary Science, 2024)
Porcine reproductive and respiratory syndrome virus (PRRSV) remains one of the major threats to swine industry, resulting in huge economic losses worldwide. Currently, PRRSV has diversified into multiple lineages with characteristics of extensive recombination in China. In this research, three virus strains were isolated and four virus whole genome sequences were generated and analyzed from clinical samples collected in Gansu province of China in 2023. The four virus strains were designated GSTS4-2023, GSLX2-2023, GSFEI2-2023, and GSBY4-2023. Phylogenetic analysis based on ORF5 sequences showed that GSTS4-2023, GSLX2-2023, GSFEI2-2023, and GSBY4-2023 shared 91.7%, 91.2%, 93.2%, and 92.9% homology with NADC30 strain respectively, and belonged to lineage 1 of PRRSV-2. In addition, one amino acid deletion was observed at position 33 in ORF5 of GSTS4-2023, GSLX2-2023 and GSFEI2-2023. Moreover, amino acid alignment of the four strains showed a typical discontinuous 131-amino acid (aa) deletion in NSP2 for NADC30-like virus strains. Recombination analysis revealed that all four strains originated from NADC30 (lineage 1), with their minor parents coming from JXA1-like strains (lineage 8), VR-2332-like strains (lineage5) and QYYZ-like strains (lineage3). Finally, the three isolated virus strains, GSTS4-2023, GSLX2-2023 and GSFEI2-2023 showed relatively low levels of replication in cell culture. Our findings provide important implications for the field epidemiology of PRRSV.